2020
DOI: 10.1177/0021998320938850
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate effects on the mechanical behavior of single-lap glass/carbon nanofiber/epoxy composite bolted joints

Abstract: In the present research, effects of applying strain rate on the mechanical behavior of single-lap glass/CNF/epoxy composite bolted joints including, damage initiation bearing stress, 2% offset bearing strength, ultimate bearing strength, bearing chord stiffness, ultimate bearing strain, and energy absorption were studied. To this end, a comprehensive experimental program was conducted. The protruding head bolt was used, the clearance was considered to be near fit and a finger-tight bolt condition was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the effect of strain rate on the average mechanical response of GFRP under varying loading conditions is extensively studied in literature. [14][15][16][17][18][19][20][21][22] It is observed that the dynamic loading has an adverse effect on the load-bearing capacity of GFRPs. 23 Brittle failures of fibers, matrix cracking, interfacial, and interlaminar delamination are found to be the dominant failure modes in GFRPs at varying strain rates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effect of strain rate on the average mechanical response of GFRP under varying loading conditions is extensively studied in literature. [14][15][16][17][18][19][20][21][22] It is observed that the dynamic loading has an adverse effect on the load-bearing capacity of GFRPs. 23 Brittle failures of fibers, matrix cracking, interfacial, and interlaminar delamination are found to be the dominant failure modes in GFRPs at varying strain rates.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several experimental investigations of all three joining methods using different material substrates, adhesives, and bolt configurations for both quasi-static and high-rate loading conditions [2][3][4][5][6][7][8][9]. Most of these investigations used servo-hydraulic testing machines.…”
Section: Introductionmentioning
confidence: 99%
“…11 In this case, the strain rate can significantly influence the mechanical performance of the composite. 12,13 With increasing the strain rate, the yield stress of resin increases, 14 accompanied with the plateau stress 15 and the dynamic compressive strength 16 of the composite increases. A positive linear relationship between strength and strain rate 17 or logarithmic strain rate 18 has been found.…”
mentioning
confidence: 99%